PENGARUH LATIHAN STANDING BARBELL TRICEPS EXTENTION TERHADAP KEKUATAN OTOT LENGAN DAN BAHU DALAM MELAKUKAN SERVIS ATAS PADA TIM BOLA VOLI PUTRA SMP NEGERI 34 PEKANBARU - Sagala, Henni Epelina Martogi; Slamet, Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this researh it still a lack of muscle strength of the arms and shoulders during serving up a ball can not pass trough the net Based on these problems the writer give the standing barbell triceps extention exercises to know the effect of standing barbell triceps extention on muscle arm strength and shoulder in doing up service on the men's volleyball team of SMP Negeri 34 Pekanbaru doing service up get the maximum result. This type of research is experiment with design one group preteset-posttest design. Population in this research the men's volleyball team of SMP Negeri 34 Pekanbaru is the entire population of 12 people. While the sample technique used total sampling where all the population is sample. The sample in this study amounted to 12 people of the men's volleyball team of SMP Negeri 34 Pekanbaru. The instrument use in this research to test of muscle strength of the arms and shoulders is expanding dynamometer test. After that, the data is processed with statistic normality test with liliefors test at significance test level α (0,05). The hypothesisis the effect effect of standing exercise barbell triceps extention on muscle arm strength and shoulder. Based on the analysis of statistical data, there are an average pretest 17,00 and posttest 20,25 with an increase 3,25. Based on t test, analysis produces thitung 10,8 and ttabel 1,796, meaning thitung> ttabel.Thus, there effect of of standing barbell triceps extention on muscle arm strength and shoulder in doing up service on the men’s volley ball team of SMP Negeri 34 Pekanbaru. .Keywords: Standing Barbell Triceps Extention, Muscle Arm and Shoulder Strength